2004
DOI: 10.1183/09031936.03.00022003
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sex on sleep-disordered breathing in adolescents

Abstract: This study was conducted to determine the influence of puberty on features of sleep-disordered breathing (SDB) in adolescents.The study was performed in a general population sample of 226 adolescents of both sexes (aged 11-19 yrs) recruited from the secondary school population of the city of Seville, Spain. Subjects were divided into two groups: 1) postpubertal, i.e. females who had undergone menarche and males in whom axillary hair development or peak height velocity had occurred w1 yr before the study; and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 33 publications
0
12
0
2
Order By: Relevance
“…In the first phase of the present study, there was no male predominance among the snorers [12], but when the population was divided by stage of pubertal development, sexrelated differences were observed among the post-pubertal adolescents, with a higher prevalence of snoring and more polygraphic disturbances in males [15]. In the current longitudinal study, a predominance of males among the habitual snorers (14 out of 18) was found at long-term follow-up.…”
Section: Discussionmentioning
confidence: 54%
See 3 more Smart Citations
“…In the first phase of the present study, there was no male predominance among the snorers [12], but when the population was divided by stage of pubertal development, sexrelated differences were observed among the post-pubertal adolescents, with a higher prevalence of snoring and more polygraphic disturbances in males [15]. In the current longitudinal study, a predominance of males among the habitual snorers (14 out of 18) was found at long-term follow-up.…”
Section: Discussionmentioning
confidence: 54%
“…A previously reported questionnaire [12][13][14][15] (see online supplementary data) was used in the follow-up study. The questionnaire was completed by a technician, and data were provided by the subject and their parents.…”
Section: Questionnairementioning
confidence: 99%
See 2 more Smart Citations
“…According to Wolkove et al [25], older people increase occurrence of obesity predisposing to upperairway narrowing, decline in muscle tone enhancing upper-airway collapsibility, and impair pharyngeal sensory discrimination to make a persistence of upper-airway collapse during sleep. Fuentes-Pradera et al [26] explained that sex hormone might influence neuromuscular control of upper airway and central pattern of body fat distribution, which related to OSA. However, in our study, the differences disappeared after adjusting for BMI.…”
Section: Discussionmentioning
confidence: 99%